Manowce polskiej egiptologii XIX wieku. Jerzego Ręczyńskiego „przekład” tekstu kamienia z Rosetty - Kaczmarek, Hieronim (Folia Praehistorica Posnaniensia, 2018)
The paper is one of a number of publications devoted to perception of the history of ancient Egyptian civilization in Poland by the end of the 19th century. It presents Jerzy Ręczyński’s (1905-1899) ‘attempts’ to study Egyptian inscriptions (the Rosetta Stone), results of which have to be absolutely rejected according to contemporary research standards.